2018
DOI: 10.1016/j.jad.2017.10.008
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of treatment outcome in depression in later life: A systematic review and meta-analysis

Abstract: Baseline depression severity, co-morbid anxiety, executive dysfunction, current episode duration, early improvement, physical illnesses and age were reported as statistically significant predictors of treatment outcomes. Only the first three were significant in meta-analyses. Subgroup analyses showed differences in predictor effect between biological and psychosocial treatment. However, high heterogeneity and small study numbers suggest a cautious interpretation of results. These predictors were associated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
49
5
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(61 citation statements)
references
References 140 publications
5
49
5
1
Order By: Relevance
“…There is an abundance of evidence assessing the effectiveness of treatments for late-life depression. However, frailer older adults represent an understudied subgroup of this population, and there is evidence that physical illness, older age, and impaired executive functioning can negatively impact pharmacological and non-pharmacological treatment outcomes (Tunvirachaisakul et al, 2017). Antidepressants only appear to be effective when studied as a class, rather than individual drug types, and when reviews use an "older adult" threshold of 55 + years rather than 65 + (Jonsson et al, 2016;Kok et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…There is an abundance of evidence assessing the effectiveness of treatments for late-life depression. However, frailer older adults represent an understudied subgroup of this population, and there is evidence that physical illness, older age, and impaired executive functioning can negatively impact pharmacological and non-pharmacological treatment outcomes (Tunvirachaisakul et al, 2017). Antidepressants only appear to be effective when studied as a class, rather than individual drug types, and when reviews use an "older adult" threshold of 55 + years rather than 65 + (Jonsson et al, 2016;Kok et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, depression and anxiety may worsen during the “off periods” that PD patients frequently experience during dopaminergic treatment . This complex presentation has been associated with nonresponse to depression treatment and with high rates of disability and depressive relapse . Given that 56% of PWP in this trial had a comorbid anxiety disorder and the average length of the current depressive episode was 2 years, the current findings reflect the suitability of PD‐informed CBT to addressing dPD's heterogeneity and psychiatric complexity.…”
Section: Discussionmentioning
confidence: 81%
“…In addition, case-control studies have revealed a positive correlation between depression and subsequent onset of Alzheimer's disease in patients with LOD [8]. A recent meta-analysis revealed that baseline depression severity, co-morbid anxiety, executive dysfunction, current episode duration, early improvement, physical illnesses and age were statistically significant predictors of treatment outcomes of patients with LOD [9].…”
Section: Introductionmentioning
confidence: 99%